Institutional Support of City Innovation in Silesia - Sanetra-Półgrabi, Sabina (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
Polish cities deal with a lot of economic as well as social problems. First of all, they have to adapt to the changes that occur all around Europe. They start from a much worse position than the better developed cities of the European Union, mainly because of infrastructural negligence. Secondly, the cities deal with same problems as other European cities, especially the unemployment of univer- sity graduates. The potential solution for this situation is not only money, but also a favorable attitude towards innovations. City innovation can be examined in different ways. Usually the presence of particular institutions is taken into consideration. Thanks to various financial and non-financial mechanisms, the institutions support commercialization of technology, the presence of companies producing high technology and the use of Union fund that determines which cities become centres of innovation in different contests, e.g. Leaders of Innovation and Development. Such institutions function in Silesia and are very successful. These are mainly research and development entities, industrial and science-technology parks and also institutions of business environment. The article is written for the purpose of showing how impor- tant the institutions are in Silesia. At the beginning the key words relating to innovation are explained.